KEPASTIAN HUKUM TERHADAP TENAGA KERJA YANG MENGALAMI PEMUTUSAN HUBUNGAN KERJA SEPIHAK PASCA TERBITNYA UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Hendrik Hendrik; Gatut Hendro; Putra Hutomo (LPPM Institut Pendidikan Nusantara Global, 2023)
Since the enactment of Law Number 11 of 2020 concerning Job Creation (hereinafter referred to as the Omnibus Law) companies can carry out unilateral layoffs on the grounds of efficiency, whether followed by company closure or not followed by company closure due to losses, so that it becomes a question of how to resolve disputes over unilateral termination of employment disputes and also regarding legal protection for workers who have experienced unilateral termination of employment since the enactment of Law Number 11 of 2020 concerning Job Creation. As an analysis knife, the theory of legal protection and the theory of dispute resolution are used to analyze the problem. The type of research in this thesis is normative juridical, namely legal research that places law as a system of norms (principles, norms, rules from laws and regulations, court decisions, and doctrines (teachings). The approaches used in legal research are the statutory approach, conceptual approach, analytical approach, case approach. Mawey Z. Alfa in his research states that layoffs are the cessation of individuals as members of an organization accompanied by the provision of financial rewards by the organization concerned. PHK must be preceded by notification of the plan and also look for ways to avoid unilateral layoffs by the company, if examined based on the provisions of Article 6 and Article 7 of Law Number 2 of 2004, consensus deliberation can be carried out using the principle of kinship between workers and employers. If there is an agreement between the worker and the employer, it can be outlined in an agreement between the two parties, while in the provisions of Article 151 Paragraphs (1) through (4) of the Job Creation Law there is a clear mechanism regarding the planning processes until the implementation of layoffs in a company. In Paragraph (4) it is emphasized that if the bipartite negotiation process does not reach an agreement, layoffs are carried out through the next stage in accordance with the industrial relations dispute mechanism. Disputes over unilateral termination of employment are resolved by bipartite negotiations so that the settlement process is calm and there is no conflict between workers and employers that causes unrest.